A180 PREVALENCE AND RELEVANCE OF FINANCIAL CONFLICTS OF INTEREST AMONG CLINICAL PRACTICE GUIDELINES IN NUTRITION. (15th March 2019) - Sasson, A N; Scaffidi, M A; Bansal, R; Dhillon, J; Khan, R; Grover, S C
Abstract: Background: There is broadly documented evidence that industry funding can influence clinical practice guidelines (CPGs). This is seen in many drug-industry sponsored research but the role in nutrition science literature is unclear. We reviewed the prevalence and relevance of financial conflicts of interest (FCOI) in CPGs published by the top global nutrition societies. Aims: Our aim is to improve the current FCOI disclosure practices in nutrition CPG development. Methods: We performed a cross-sectional analysis of FCOIs declared by nutrition CPG authors. We assessed the prevalence of declared and undeclared FCOI by guideline authorship and determined relevancy of sponsorship to the guideline content. We assessed adherence to the National Academy of Medicine (NAM) practice standard which states CPG development and funding should be explicitly stated and publicly available. Results: We identified 19 guidelines with 195 authors. Analysis revealed 8 (42%) guidelines with stated disclosures, half of which were explicitly declared in the CPG and the other half whereby declarations were inaccessible to the public. In respect of those guidelines whereby disclosed and undisclosed FCOI could be assessed, 100% of the stated disclosures were relevant to the authored guideline and 66% of undisclosed relationships were relevant. There is some evidence of undisclosed FCOI where studies state there were none to declare. This data suggests that almost half of the recent nutrition CPGs reviewed do not adhere to NAM transparency standards. Conclusions: Many authors of recently published nutrition CPGs have relevant FCOI, both disclosed and undisclosed. We have determined that transparency could be improved to achieve compliance with the NAM standards and mitigate potential for bias that could affect research integrity. Funding Agencies: None